1986
DOI: 10.1192/bjp.149.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Positive and Negative Syndromes in Chronic Schizophrenia

Abstract: Positive and negative syndromes were studied in relation to demographic, historical, genealogical, clinical, psychometric, extrapyramidal, and follow-up measures of 101 chronic schizophrenic patients. The criterion scales proved to be reliable, normally distributed, and strongly correlated with general psychopathology, but otherwise inversely related to one another. Multiple regression analysis identified sets of 4-6 independent variables that explained 74%-81% of the scales' variance. A positive syndrome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(100 citation statements)
references
References 38 publications
5
90
1
4
Order By: Relevance
“…Furthermore, a number of studies have found males more likely to exhibit 'negative' features (Kay et al 1986;Goldstein & Link, 1988;Nasrallah & Wilcox, 1989;Haas et al 1989), though not all have concurred (reviewed by Pogue-Geile & Zubin, 1988).…”
Section: Presentation and Outcomementioning
confidence: 99%
“…Furthermore, a number of studies have found males more likely to exhibit 'negative' features (Kay et al 1986;Goldstein & Link, 1988;Nasrallah & Wilcox, 1989;Haas et al 1989), though not all have concurred (reviewed by Pogue-Geile & Zubin, 1988).…”
Section: Presentation and Outcomementioning
confidence: 99%
“…Clinical characteristics: duration of illness and psychotic symptoms based on the Positive and Negative Syndrome Scale (PANSS). 40 The PANSS was decomposed into 5 factors (positive, negative, hostility-excitation, cognitive and depression factors), which are of specific interest for our study because of their potential link to insight. …”
Section: Data Collectionmentioning
confidence: 99%
“…There is reason to believe, however, that the overlap is not artifactual. Indeed, studies by our group (Kay et al, 1986) have indicated a significant association between negative syndrome and extrapyramidal ratings and the negative score on the Positive and Negative Syndrome Scale (PANSS) even though this excludes motor items (Kay et al, 1987). Similarly, Hoffman et al ( 1987) found a strong association between negative symptoms and Parkinsonism which he argued reflected an "underlying pathophysiological relationship" and not merely scale item similarity or difficulty in distinguishing negative symptoms from Parkinsonism.…”
Section: Negative Schizophrenia Of Parkinsonismmentioning
confidence: 97%